DESAIN PENINGKATAN KOMPETENSI PEDAGOGIK DAN PROFESIONALISME PENDIDIK PENDIDIDKAN AGAMA ISLAM (PAI) DI SUKOREJO GONDANG LEGI MALANG - Imam Safi'i (VICRATINA, 2022)
The background of this research is to find some indicators of teachers' pedagogy and professionalism in performing their main teaching task, namely, teachers' understanding of learning strategies and PAI teachers' motivation to learn. improve personal quality. This research is a type of qualitative research that uses descriptive qualitative research methods. The method used in this study uses interviews, observation and documentation. Data analysis techniques used to collect data through data reduction, data presentation, and drawing conclusions. Data presented in descriptive form. Verification of the validity of the data through triangulation of sources and technical triangulation. The conclusions of this study indicate that: The design to increase the pedagogical competence and professionalism of Islamic religious education teachers in Global Islamic Schools, namely: 1) for pedagogical competence and teaching professionalism in Global Islamic Schools is quite good and is in accordance with the government recommendations 2) to organize the improvement of the pedagogical competence and professionalism of the principal has quite an important role, such as MGMP 3) the evaluation of the increase of the pedagogical competence and professionalism of the main teacher forms a team of assessment coordinators, the team is formed to find out to what extent the teacher's skills are.